Identification of glucocorticoid receptors as potential modulators of parasympathetic and sympathetic neurons within rat intracardiac ganglia - Mousa, Shaaban A.; Dehe, Lukas; Aboryag, Noureddin; Shaqura, Mohammed; Beyer, Antje; Schäfer, Michael; Treskatsch, Sascha (Frontiers in Neuroanatomy, 2022)
Background Emerging evidences indicate that glucocorticoid receptors (GR) play a regulatory role in cardiac function, particularly with regard to the autonomic nervous system. Therefore, this study aimed to demonstrate the expression and the precise anatomical location of GR in relation to the parasympathetic and sympathetic innervations of the heart. Methods The present study used tissue samples from rat heart atria to perform conventional reverse-transcriptase polymerase chain reaction (RT-PCR), Western blot, and double immunofluorescence confocal analysis of GR with the neuronal markers vesicular acetylcholine transporter (VAChT), tyrosine hydroxylase (TH), calcitonin gene-related peptide (CGRP) as well as the mineralocorticoid receptor (MR). Results Double immunofluorescence labeling revealed that GRs were co-expressed with VAChT in parasympathetic principal neuronal somata and nerve terminals innervating atrium. Also, GR colocalized with the sympathetic neuronal marker TH in a cluster of small intensely fluorescent (SIF) cells, on intracardiac nerve terminals and in the atrial myocardium. GR immunoreactivity was scarcely identified on CGRP-immunoreactive sensory nerve terminals. Approximately 20% of GR immunoreactive neuronal somata co-localized with MR. Finally, conventional RT-PCR and Western blot confirmed the presence of GR and MR in rat heart atria. Conclusion This study provides evidence for the existence of GR predominantly on cardiac parasympathetic neurons and TH-immunoreactive SIF cells suggesting a functional role of cardiac GR on cardiovascular function by modulation of the cardiac autonomic nervous system.